MANAJEMEN BENCANA INTERNASIONAL: TINJAUAN HISTORIS DAN TANTANGAN BAGI INDONESIA - Pratama, Patrya (Global: Jurnal Politik Internasional, 2010)
There are at least three points that this article seeks to explain. Firstly, it intends to provide historical precedence regarding disaster management. Elaboration includes stories of disaster management across civilizations. The goal is to provide reader that disaster management has always been vital in maintaining human existence; thus, the study of International Relations could not afford to ignore the issues if it wants to remain relevant. Secondly, this article attemps to provide readers the establishment of the current international disaster management landscape. There are international level (through the United Nations agency) and regional level arrangements of disaster management that we should take into account. The perspective of global governance will be emphasized in understanding the issue in order to appreciate the fact of how diffused disaster management resources are in contemporary situation. Lastly, the writer takes the example of Indonesia in an attempt to argue that nation states are still the backbone of putting together all disaster management resources to be manageable and effective in reducing human and material losses due to disaster. There are at least three points that this article seeks to explain. Firstly, it intends to provide historical precedence regarding disaster management. Elaboration includes stories of disaster management across civilizations. The goal is to provide reader that disaster management has always been vital in maintaining human existence; thus, the study of International Relations could not afford to ignore the issues if it wants to remain relevant. Secondly, this article attemps to provide readers the establishment of the current international disaster management landscape. There are international level (through the United Nations agency) and regional level arrangements of disaster management that we should take into account. The perspective of global governance will be emphasized in understanding the issue in order to appreciate the fact of how diffused disaster management resources are in contemporary situation. Lastly, the writer takes the example of Indonesia in an attempt to argue that nation